A silver staining procedure for nucleic acids in polyacrylamide gels without fixation and pretreatment - An, Z.W.; Xie, L.L.; Cheng, H.; Zhou, Y.; Zhang, Q.; He, X.G.; Huang, H.S.
Silver staining of nucleic acid has been widely used in molecular marker analysis such as simple sequence repeat (SSR), single-strand conformation polymorphism (SSCP), and amplified fragment-length polymorphism (AFLP). Many alternatives to silver staining methods have been described, but these methods are not efficient or cost-effective. Here we report a silver staining method that requires less than 10 min for one gel and can save chemicals as well. It has a detection limit of approximately 5.6 pg of DNA/mm2 in nondenaturing polyacrylamide gels and 12.8 pg/mm2 in denaturing polyacrylamide gels.